شعر"دع الأيام" في ديوان الإمام الشافعى (دراسة تحليلية السيميائية لشارلز موريس) - Aula, Munib (Journal of Arabic Language and Literature (ALLAIS), 2022)
This study focuses on الإمام Syafi'i's poem entitled "Da'il Ayyam" with the semotic analysis of Charles Morris. This study aims to determine and describe the meaning of the sign contained in the poem "Da'il Ayyam" written by Imam Al-Shafi'i. This research is a descriptive-analytical research, which is a systematic decomposition of the data obtained, providing understanding and interpretation so that readers can understand it well. without intending to draw general conclusions or generalizations. In this thesis, the researcher concludes that according to Morris's semiotic theory, from the general syntactic level, the number of insyyyah tholabiyyah is the number of insyyyah tholabiyyah, while the specific syntax is dominated by the 'atof' structure and the terms of answer. From the semantic level, it is the semantics of المرجعي, namely humans and all the events they face in the world. And from the pragmatic level, it is pragmatic in terms of background, namely Imam Shafi'i's life journey to accept destiny.